Probing the catalytic activity of pristine and doped Pd and Ni metal clusters towards H2O molecule - Samal, Pragnya Paramita; Joshi, Krati; Kaliaperumal, Selvaraj; Krishnamurty, Sailaja (Computational and Theoretical Chemistry, 2019)
Electrolysis of H2O to produce molecular hydrogen, the most environment friendly and energy efficient fuel, using cost effective catalysts is one of the major global research challenges. To date, Pt remains the best suitable and yet highly expensive electro-catalyst for hydrogen evolution reaction. Design of an alternative cost-effective catalyst requires a fundamental molecular level understanding of the water molecule adsorption and its activation. In that context, we examine the adsorption and activation of water molecule on model alternative catalysts namely, Ni-6 and Pd-6 clusters using density functional theory based methodology. Ni-6 and Pd-6 clusters and their singly doped counterparts are used for this study. Mo, W, Fe, Co and Cu are used as doping elements. To quantify the influence of medium (neutral and alkaline) on the activation of the water molecule, Ni based clusters are considered in neutral and anionic states, respectively. The activity of these clusters towards H2O molecule is evaluated in terms of the adsorption energy, charge transfer, bandgap, red shift in O-H stretching frequency and dissociation barriers for H2O. The studies demonstrate that doping with Co in all the studied clusters (Pd-6, Ni-6 and anionic Ni-6) increases their activity. Best activity is noted for Fe doped neutral Ni b clusters with a dissociation barrier of 5.76 kcal/mol.
Keywords: Activation barrier; Ni clusters; O-H activation; Pd clusters; Red shift of O-H stretching frequency; Water adsorption